2011
DOI: 10.1242/jcs.076026
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase–nitric oxide signaling mediates the mitogenic activity of Rac1 during endochondral bone growth

Abstract: SummaryCoordinated proliferation and differentiation of growth plate chondrocytes controls endochondral bone growth and final height in humans, and disruption of this process results in diseases of the growing and adult skeleton, such as chondrodysplasias or osteoarthritis. We had shown recently that chondrocyte-specific deletion of the gene Rac1 in mice leads to severe dwarfism due to reduced chondrocyte proliferation, but the molecular pathways involved remained unclear. Here, we demonstrate that Rac1-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Inhibition of Rac1 expression in micromass culture resulted in reduced mRNA levels of the chondrogenic markers collagen II and aggrecan, and decreased accumulation of glycosaminoglycans indicating that Rac1 promotes chondrogenesis [28]. Rac1-deficient chondrocytes had severely reduced levels of inducible nitric oxide synthase protein (iNOS) and nitric oxide production [29]. Mice deficient for iNOS had reduced chondrocyte proliferation and resembled the phenotype of Rac1-deficient growth plates.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Rac1 expression in micromass culture resulted in reduced mRNA levels of the chondrogenic markers collagen II and aggrecan, and decreased accumulation of glycosaminoglycans indicating that Rac1 promotes chondrogenesis [28]. Rac1-deficient chondrocytes had severely reduced levels of inducible nitric oxide synthase protein (iNOS) and nitric oxide production [29]. Mice deficient for iNOS had reduced chondrocyte proliferation and resembled the phenotype of Rac1-deficient growth plates.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is necessary for development and maintenance of cartilage [26], and its chondrocyte-specific deletion results in severe dwarfism in mice [27]. In response to fibronectin fragments, it is reported that Rac1 is required for the production of MMP13 in chondrocytes [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although low and variable levels of nitric oxide are essential during endochondral ossification, catabolic and homeostatic activity in human cartilage (Amin et al, 1999;Wang et al, 2011), high levels of NO have detrimental effects in cartilage . Granted that HMGB1 can bind to a multitude of known receptors in chondrocytes, the functional receptor for HMGB1 in human OA-affected cartilage remains elusive.…”
Section: Figmentioning
confidence: 99%